PERANCANGAN MESIN PENCACAH BRIKET SAMPAH DENGAN MENGGUNAKAN KONSEP INOVASI FRUGAL DI PONDOK PESANTREN CIPASUNG TASIKMALAYA - Muslimah, Ajeng Sabarini; Aripin, Wahyu Teri; Alam, Muhammad Samsam Purnama (Cipasung Techno Pesantren: Jurnal Ilmiah, 2024)
Cipasung Islamic Boarding School is one of the Islamic boarding schools in Cipakat Village, Singaparna District, Tasikmalaya Regency. As the number of students and residents increases, the amount of waste generated also increases. Currently, what needs to be done is not to be hostile to waste, but to find a way to speed up the waste decomposition process and utilize waste that can still be recycled. Therefore, it is necessary to design a waste shredder machine, considering one of the concepts, namely Frugal Innovation. The results of the waste shredder machine have a waste shredding capacity specification of 100 kg/hour, the waste shredding process is carried out through a drive transmission using a 4.0 hp 118 cc 3,600 rpm satoo gasoline motor with 12 dynamic blades, used drum container, wheels and shift levers. With a total price of the waste shredder machine of IDR 6,458,000. The results of the analysis of the design machine have advantages in terms of price and the addition of wheel and lever features, compared to machines on the market.